Autobiographical Authority and the Politics of Narrative - Renée Larrier (Studies in 20th & 21st Century Literature, 1991)
Autobiographical narratives, which include autobiography, autobiographical novel, memoir, and chronicle, constitute a major genre in African francophone literature. Informed by history, they do not celebrate personal accomplishment, but rather accentuate the group experience. These self-stories rely on realistic representation in order to document events for future generations and function to correct stereotypical misconceptions—therein lies their political consciousness.
Keywords: Autobiographical narratives; autobiography; autobiographical novel; memoir; chronicle; African; French; Francophone Literature; genre; personal; accomplishment; history; group experience; self-stories; realistic; representation; document; future; generations; stereotypical misconception; stereotype; political consciousness